2014
DOI: 10.1002/ange.201409606
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Air‐Stable, Volatile Uranium(IV) and (VI) Compounds and Their Gas‐Phase Conversion To Uranium Oxide Films

Abstract: Four air-stable, volatile uranium heteroarylalkenolates have been synthesized and characterized by three synthetic approaches and their gas phase deposition to uranium oxide films has been examined. Scheme 1. Structure and stabilizing factors of b-heteroarylalkenolates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 83 publications
(17 reference statements)
0
10
0
Order By: Relevance
“…Exciting progress in the chemical vapor deposition (CVD) of uranium oxides using volatile uranium(IV) compounds has been reported. [33][34][35] In 2014, Mathur, Evans, and co-workers described the gas phase conversion of air-stable uranium(IV) β-heteroarylalkenolates to form UO 3 and U 3 O 8 films using CVD. 33 Later, Mathur et al demonstrated that volatile uranium (IV) amidinate complexes could be used for the CVD of phasepure UO 2 thin films.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Exciting progress in the chemical vapor deposition (CVD) of uranium oxides using volatile uranium(IV) compounds has been reported. [33][34][35] In 2014, Mathur, Evans, and co-workers described the gas phase conversion of air-stable uranium(IV) β-heteroarylalkenolates to form UO 3 and U 3 O 8 films using CVD. 33 Later, Mathur et al demonstrated that volatile uranium (IV) amidinate complexes could be used for the CVD of phasepure UO 2 thin films.…”
Section: Introductionmentioning
confidence: 99%
“…[33][34][35] In 2014, Mathur, Evans, and co-workers described the gas phase conversion of air-stable uranium(IV) β-heteroarylalkenolates to form UO 3 and U 3 O 8 films using CVD. 33 Later, Mathur et al demonstrated that volatile uranium (IV) amidinate complexes could be used for the CVD of phasepure UO 2 thin films. More recently, the uranium(VI) alkoxide complex U(O t Bu) 6 was shown to undergo reductive decomposition through CVD to give UO 2 films.…”
Section: Introductionmentioning
confidence: 99%
“…The lack of simple and efficient thin-film deposition methods for UO 2 impedes radiation damage investigation at the nanoscale level. Safety concerns for radioactive UO 2 limit the available deposition methods to magnetron sputtering (MS), chemical vapor deposition (CVD), , and polymer-assisted deposition (PAD). , MS allows deposition of films with preferred crystallographic orientation on selected single-crystalline substrates ,, and requires high-vacuum instrumentation and special handling conditions for pyrophoric metallic uranium as a source material. The CVD method uses toxic volatile organouranium precursors. ,, Films exhibit good adhesion to substrates, but they often contain other oxides of uranium.…”
Section: Introductionmentioning
confidence: 99%
“…Safety concerns for radioactive UO 2 limit the available deposition methods to magnetron sputtering (MS), chemical vapor deposition (CVD), , and polymer-assisted deposition (PAD). , MS allows deposition of films with preferred crystallographic orientation on selected single-crystalline substrates ,, and requires high-vacuum instrumentation and special handling conditions for pyrophoric metallic uranium as a source material. The CVD method uses toxic volatile organouranium precursors. ,, Films exhibit good adhesion to substrates, but they often contain other oxides of uranium. The PAD method uses a solution of uranyl nitrate and polyethylenimine to be deposited by spin coating. ,,, Further burning off the organic residues and obtaining crystalline UO 2 require a slow (1 °C/min) heating to high temperatures (1000 °C).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation